Recent advances in precision medicine for pancreatic ductal adenocarcinoma - Hayashi, Hiromitsu (Ann Gastroenterol Surg, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is one of the leading causes of cancer mortality worldwide. Although advances in systemic chemotherapy for PDAC have improved survival outcomes for patients with the disease, chemoresistance is a major treatment issue for unselected PDAC patient populations. The existence of heterogeneity caused by a mixture of tumor cells and stromal cells produces chemoresistance and limits the targeted therapy of PDAC. Advances in precision medicine for PDACs according to the genetics and molecular biology of this disease may represent the next alternative approach to overcome the heterogeneity of different patients and improve survival outcomes for this poor prognostic disease. The genetic alteration of PDAC is characterized by four genes that are frequently mutated (KRAS, TP53, CDKN2A, and SMAD4). Furthermore, several genetic and molecular profiling studies have revealed that up to 25% of PDACs harbor actionable alterations. In particular, DNA repair dysfunction, including cases with BRCA mutations, is a causal element of sensitivity to platinum‐based anti‐cancer agents and poly‐ADP ribose polymerase (PARP) inhibitors. A deep understanding of the molecular and cellular crosstalk in the tumor microenvironment helps to establish scientifically rational treatment strategies for cancers that show specific molecular profiles. Here, we review recent advances in genetic analysis of PDACs and describe future perspectives in precision medicine according to molecular subtypes or actionable gene mutations for patients with PDAC. We believe the breakthroughs will soon emerge to fight this deadly disease.